Taxonomic study of the genus Ziziphus Mill. (Rhamnaceae) of Bangladesh - Ara, Hosne; Hassan, Md. Abul; Khanam, Mahbuba (Bangladesh Journal of Plant Taxonomy, 2008)
A taxonomic account of six species of Ziziphus Mill., viz. Z. funiculosa Buch.-Ham. ex Lowson, Z. glabrata Heyne ex Roth, Z. mauritiana Lam., Z. oenoplia (L.) Mill., Z. rugosa Lam., and Z. xylopyrus (Retz.) Willd. occurring in the flora of Bangladesh has been given. A dichotomous key to the species has been furnished. An updated nomenclature including important synonyms, selected references, description of the taxa along with illustrations, ecological notes, specimens examined and geographical distribution have been provided. Bangla and English names, flowering and fruiting periods, chromosome number and economic importance have also been presented where available. Keywords: Ziziphus; Taxonomy; Bangladesh DOI: 10.3329/bjpt.v15i1.917 Bangladesh J. Plant Taxon. 15(1): 47-61, 2008 (June)